2013
DOI: 10.1177/1474651413502685
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide pancreatitis: The ABCD nationwide liraglutide audit

Abstract: Introduction: There is concern that glucagon-like peptide-1 (GLP1) receptor agonists may be associated with acute pancreatitis. The data from the ABCD nationwide liraglutide audit (November 2009-June 2013; 6010 patients) provide an opportunity to assess the extent of the problem in routine clinical practice in the UK. Methods: At every patient visit, audit-contributors were invited to submit, via an electronic form, clinical data collected as part of routine clinical practice, including data on possible side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Parts of this study were presented at the 2012 Joint Meeting of the American Pancreatic Association and International Association of Pancreatology, Miami, FL, 31 October-3 November 2012 (49). These data were subsequently incorporated into studies published by other authors (16,24). A short statement on six of the cases included in the case reviews was included in a letter to The Annals of Pharmacotherapy (35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parts of this study were presented at the 2012 Joint Meeting of the American Pancreatic Association and International Association of Pancreatology, Miami, FL, 31 October-3 November 2012 (49). These data were subsequently incorporated into studies published by other authors (16,24). A short statement on six of the cases included in the case reviews was included in a letter to The Annals of Pharmacotherapy (35).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a liraglutide audit conducted by the Association of British Clinical Diabetologists reported that after 3,720 years of exposure to liraglutide across 6,010 patients, four cases of possible pancreatitis were documented. Likely causes were identified in three patients, and one patient had no etiological cause (24). The authors concluded that "people with type 2 diabetes are at greater risk of acute pancreatitis (hazard ratio between 1.5 and 2.8).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The total incidences of definite or possible reported pancreatitis in the audits were 0.120 and 0.108 cases per 100 patient years of exposure in the exenatide26 and liraglutide27 audits, respectively. The audits had the strength that they allowed detailed information about reported cases to be obtained – contributors to the audit reporting the cases were contacted and full detail obtained from the hospital notes.…”
Section: Abcd Nationwide Audits Of Glp‐1 Receptor Agonistsmentioning
confidence: 94%
“…The audits had the strength that they allowed detailed information about reported cases to be obtained – contributors to the audit reporting the cases were contacted and full detail obtained from the hospital notes. It was noteworthy that in most reported cases there were other causes for the pancreatitis, in particular gallbladder disease, alcoholism and hypertriglyceridaemia 26,27. After this detailed investigation of each reported case, the exenatide audit (6717 patients) and the ongoing liraglutide audit (6010 patients as of 1 July 2013) each had one unexplained case representing incidences of unexplained pancreatitis in the ABCD audits of 0.030 and 0.027 cases per 100 patient years of exposure to exenatide26 and liraglutide, respectively 27.…”
Section: Abcd Nationwide Audits Of Glp‐1 Receptor Agonistsmentioning
confidence: 98%